(untitled) (Web of Teachers: Inderscience Research, 2026)
This article examines the theoretical foundations and practical implementation of a structured technology for integrating authentic materials into foreign language teaching at the university level. Despite widespread recognition of authentic materials’ benefits, systematic approaches to their pedagogically sound integration remain underdeveloped. This study proposes a comprehensive four-dimensional framework (Selective, Adaptive, Interactive, and Evaluative components) designed to optimize the incorporation of authentic resources into language curricula. The research employed a mixed-methods approach, involving 180 undergraduate students across three universities during the 2023-2024 academic year. Experimental results demonstrate that the proposed integration technology significantly enhances language proficiency (p < 0.01), with experimental groups showing 34% improvement in listening comprehension, 29% in communicative competence, and 31% in cultural awareness compared to control groups using traditional textbook-based instruction. The study identifies key parameters for material selection, adaptation strategies, and digital tool integration, offering practical recommendations for language educators.